SarA based novel therapeutic candidate against Staphylococcus aureus associated with vascular graft infections - Arya, Rekha; Ravikumar, R.; Santhosh, R. S.; Princy, S. Adline (Frontiers in Microbiology, 2015)
Despite advances and amalgamation of various fields to develop novel antimicrobial agents, multi-drug resistant (MDR) Staphylococcus aureus remains one of the most significant pathogen. Staphylococcal accessory regulator A (SarA) belongs to the family of global regulatory systems which regulates an array of virulence genes expression in Staphylococcus aureus. A structure based screening of novel lead compounds was employed to design potential small molecule inhibitor that bind to the winged helix DNA binding region of the SarA. The best small molecule inhibitor, SarABI, was initially validated in-vitro for its potency to interfere the binding of DNA with SarA. The SarABI was found to most potent at MBIC50 value of 200μg/ml where the expression of RNAIII, hld and fnbA were down-regulated. The anti-adherence property of SarABI was examined using Hep-2 cell line where no significant attachment of S. aureus was observed. Furthermore, an animal model for vascular graft infection demonstrated that SarABI significantly inhibits the colonization of multiple drug resistant Staphylococcus aureus. Our results demonstrated that the computer assisted screening is effective for identifying novel, potent, highly selective, small-molecule inhibitors that target the DNA binding region of SarA. Also, SarABI offer a novel substitute to overcome a higher degree of MDR S. aureus-induced graft rejection.